UAE-Türkiye Relations: Balanced Cooperation (2011-2023) - Mehdi Zibaei (رهیافتهای سیاسی و بین المللی)
Extended Abstract Introduction: If revolutions are considered as catalysts for changes in the international order, then the wave of Arab uprisings marked the beginning of a new regional configuration—one that, more than a decade later, continues to shape the Middle East. This wave began in Tunisia in late 2010 and quickly spread across both Arab and non-Arab countries in the region. The initial outcome of these protests was the toppling of five regimes—in Tunisia, Egypt, Libya, Yemen, and ultimately Syria—leading to a transformation in the constellation of actors in Middle Eastern international relations. Formerly central states such as Egypt, Syria, and Jordan gradually lost their dominant positions, while countries like the United Arab Emirates (UAE), Türkiye, and Qatar emerged as key regional players. Among these developments, the evolving relationship between the UAE and Türkiye stands out as particularly significant, as both have become leading actors in this new geopolitical landscape. Despite sharing a common religious identity as Sunni-majority Muslim nations, the two states have often clashed due to their differing interpretations and applications of political Islam. This geopolitical rivalry has manifested across the region—from the Eastern Mediterranean to the southern Persian Gulf, and from Syria to Libya.Methods: This study applies the theory of the balance of power to examine the relationship between Türkiye and the UAE in the aftermath of the Arab uprisings. To understand their interactions and access to national resources, it is necessary to analyze both the dynamics of balance and instances of mutual cooperation. The research employs a mixed-methods approach, combining quantitative data with qualitative analysis. The quantitative component involves statistical data related to economic, political, and other forms of bilateral engagement to identify patterns and trends. The qualitative component uses a descriptive-analytical method to explore episodes of both cooperation and conflict, drawing on content analysis of primary documents. Sources include academic books, peer-reviewed articles, theses, credible websites, and international reports from research institutions. Every effort has been made to analyze the data impartially and without bias. This hybrid methodology produces well-documented and credible insights into the UAE–Türkiye relationship and enables a more rigorous testing of the study’s hypothesis.Results and Discussion: Research findings indicate that, despite diverging approaches to regional developments and differing attitudes toward political Islam in both domestic and foreign policy, Türkiye and the UAE have maintained relatively strong economic relations by recognizing and responding to mutual needs. Within the framework of the balance of power theory, the two countries have acted as geopolitical counterweights to each other, while simultaneously forging pragmatic economic partnerships that transcend their political differences. This mutual dependency has led to notable recalibrations in national interests. Economic indicators point to a steady strengthening of cooperation over the decade following the Arab uprisings. Since 2021, these relations have expanded considerably, with both countries setting ambitious goals for bilateral trade, targeting an exchange exceeding $30 billion in the near future. Conclusion: The trajectory of UAE–Türkiye relations demonstrates that political realism views international politics as the outcome of rational choices aimed at securing national interests. In this realist framework, states can—and often do—cooperate economically even while disagreeing politically. This pragmatic approach, based on mutual needs, creates opportunities to address shared challenges in a constructive atmosphere. A review of the past decade reveals that the UAE and Türkiye have engaged in consistent and constructive economic cooperation, even while acting as mutual constraints in regional geopolitics. Acknowledging its vulnerabilities as a small, sparsely populated state, the UAE has sought to benefit from Türkiye’s regional capabilities. Conversely, Türkiye’s economic fragility and dependence on foreign investment have encouraged it to develop a relationship with the UAE characterized by political restraint and economic collaboration. This evolving model reflects a broader pattern in international relations, where states balance competition with cooperation in pursuit of long-term strategic objectives.